2015
DOI: 10.5812/traumamon.29033
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Nurses’ Requirements for Disaster Preparedness

Abstract: Background:Natural and man-made disasters affect people, communities, and health systems. Nurses play a key role in the health system and must be prepared for appropriate response in disasters.Objectives:This study was done to assess the current knowledge of nurses in emergency departments for disaster preparedness.Patients and Methods:This cross-sectional study was conducted on 110 emergency nurses working in teaching hospitals affiliated to Iran University of Medical Sciences, Tehran, Iran. A questionnaire w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
3
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 20 publications
2
40
3
7
Order By: Relevance
“…This fact leads to the conclusion that all ED staff is not properly aware about MCI triage process. Therefore, this triaging issue demands serious attention for improving any healthcare systems [9,10]. A special training is needed for the teams of disaster management like emergency medical services (EMS), civil defence department, emergency departments of the hospitals and national disaster preparedness and management services.…”
Section: Discussionmentioning
confidence: 99%
“…This fact leads to the conclusion that all ED staff is not properly aware about MCI triage process. Therefore, this triaging issue demands serious attention for improving any healthcare systems [9,10]. A special training is needed for the teams of disaster management like emergency medical services (EMS), civil defence department, emergency departments of the hospitals and national disaster preparedness and management services.…”
Section: Discussionmentioning
confidence: 99%
“…Iran is prone to the incident and is one of the ten most incident-ridden countries in the world regarding the natural disasters. According to statistics, among the 43 infamous events, 34 of them have occurred in Iran [4,5]. Iran is one of the world's most incident-ridden countries because it is located on the earthquake belt and frequently terrible earthquakes occur, the worst of them were earthquakes in Bam and Roodbar.…”
Section: Introductionmentioning
confidence: 99%
“…However, these unwanted phenomena cause mortal and financial losses, but a quick review and environmental health interventions can minimize its amount [4,5]. After most of the disasters, many people are exposed to adverse environmental effects.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that most nurses are not ready to respond to mass casualties and training and skills are not at sufficient level to make the appropriate initiative (Fothergill et al, 2005;Fung et al, 2008;Al Khalaileh et al, 2012;Diab & Mabrouk, 2015;Seyedin et al, 2015;Labrague et al, 2016).…”
Section: Nurses' Status Of Disaster Preparednessmentioning
confidence: 99%